2015
DOI: 10.1103/physrevc.92.025201
|View full text |Cite|
|
Sign up to set email alerts
|

Asymmetric nuclear matter in a parity doublet model with hidden local symmetry

Abstract: We construct a model to describe dense hadronic matter at zero and finite temperature, based on the parity doublet model of DeTar and Kunihiro, with including the iso-singlet scalar meson σ as well as ρ and ω mesons. We show that, by including a six-point interaction of σ meson, the model reasonably reproduces the properties of the normal nuclear matter with the chiral invariant nucleon mass m0 in the range from 500 MeV to 900 MeV. Furthermore, we study the phase diagram based on the model, which shows that th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 60 publications
(81 reference statements)
2
54
0
Order By: Relevance
“…Selected properties of the hadronic equations of state (T = 0, µ C = 0) and their experimental constraints (cf. [34][35][36] As evident from Figure 1, the quark matter EoS differ depending on the choice of hadronic EoS. This difference is constant for a given temperature and charge chemical potential, as to be expected from Equations (31), (35) and (36).…”
Section: The Phase Diagrammentioning
confidence: 54%
“…Selected properties of the hadronic equations of state (T = 0, µ C = 0) and their experimental constraints (cf. [34][35][36] As evident from Figure 1, the quark matter EoS differ depending on the choice of hadronic EoS. This difference is constant for a given temperature and charge chemical potential, as to be expected from Equations (31), (35) and (36).…”
Section: The Phase Diagrammentioning
confidence: 54%
“…The properties of hot and/or dense matter including neutron star matter based on the parity doublet structure are widely studied in Refs. [11,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. In [11, 18-22, 24, 26, 28], the authors studied the relation between the chiral invariant mass and the incompressibility K of nuclear matter and their results show that the empirical value K ∼ 240 MeV only when the chiral invariant mass is close to nucleon's mass, m 0 ∼ 900 MeV.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [29], six point interaction of scalar mesons was introduced and it was shown that the saturation properties are reproduced for wide region of the chiral invariant mass, i.e. 500 ≤ m 0 ≤ 900 MeV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the nucleons are introduced by the twoflavor Parity Doublet Model (PDM) [38][39][40][41][42], and nuclear matter is constructed by the one-loop approximation of the nucleon together with the meson mean fields [43][44][45][46] obtained from the eLSM. In our approach, not only the vacuum properties of nucleons but also the nuclear matter properties such as the saturation density, the binding energy per a nucleon, and the incompressibility are successfully reproduced.…”
Section: Introductionmentioning
confidence: 99%